2021
DOI: 10.1002/lary.29844
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Adult Post‐Tonsillectomy Hemorrhage Rates and the Impact of NSAID Use

Abstract: Objectives/Hypothesis Tonsillectomy is one of the most common ambulatory surgeries performed in the United States, yet the incidence of post‐tonsillectomy hemorrhage (PTH) in adults remains unclear. In addition, any association between non‐steroidal anti‐inflammatory drugs (NSAIDs) and PTH in adults is currently unknown. The aim of this study is to examine the incidence and management of adult PTH at a single academic center and to assess for any association between NSAID use and PTH in adults. Study Design Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The most important complication after extracapsular tonsillectomy is PTH. In the present study, PTH occurred in 5.80% (17/293) of patients, similar to the rates of 1.4%–11.9% reported previously 21–23 . Most previous studies have reported an increased risk of PTH after coblation extracapsular tonsillectomy 3–6,24 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The most important complication after extracapsular tonsillectomy is PTH. In the present study, PTH occurred in 5.80% (17/293) of patients, similar to the rates of 1.4%–11.9% reported previously 21–23 . Most previous studies have reported an increased risk of PTH after coblation extracapsular tonsillectomy 3–6,24 .…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, PTH occurred in 5.80% (17/293) of patients, similar to the rates of 1.4%–11.9% reported previously. 21 , 22 , 23 Most previous studies have reported an increased risk of PTH after coblation extracapsular tonsillectomy. 3 , 4 , 5 , 6 , 24 However, Glade et al 25 reported similar rates of primary and secondary PTH between coblation and electrocautery groups.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of PTH is approximately 1%–19%. PTH is regarded as a primary cause of death related with tonsillectomy and has been suggested to be a potentially lethal complication, particularly in children ( 3 , 4 ). Anemia and hemodynamic abnormalities, which can hinder the patient’s recovery and even necessitate repeat surgery, are possible PTH hazards that could have a negative psychological impact on the patient as well as physical harm.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the bleeding rate of the 432 patients prescribed NSAIDs postoperatively was nearly identical to that of the 625 patients not prescribed NSAIDs (12.6% vs. 11.7%, adjusted OR 1.01). 1 Drs Onal and Onal note that we failed to include background data regarding the use of perioperative dexamethasone and ketorolac and this is true. However, between the authors' combined experience at this institution, which spans the years 2012-present, it is believed that nearly 100% of adult tonsillectomy patients have received dexamethasone preoperatively whereas we cannot recall one instance of ketorolac being administered.…”
mentioning
confidence: 99%